Diversity in employment structures in relation to economic growth in euro-zone countries - Włodarczyk, Robert W. (Publishing House of the Wrocław University of Economics, 2009)
Structural changes result from the influence of various factors. They lead to the transformation of the whole entity under study and change its essence. Structural perspective of our surrounding is increasingly stressed in economic sciences, although it needs to be remembered that the term “structure” has become a methodological category as a whole, which applies to many fields of knowledge. Together with the development of the complexity of management, the importance of the monotony of changes, dynamics of different types of structures is growing to explain various economic dilemmas. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 452-462